(untitled) (Bulletin KNOB, 2010)
Frequently buildings are also defined by the significance deliberately attached to the building in question by the commissioning authority. This also applies for buildings from the Middle Ages and the significance of medieval religious buildings has more than once been the subject of research. We are intrigued by the question whether such a significance can also be pointed out in profane medieval buildings. We have chosen the castle-building programme of Floris V in West Friesland as our object of research. In doing so we distinguish two levels: the level of the type of castle – the quadrangular castle – and the level of the total concept. We see this concept as a spatially connected series of five castles, interrelated by the West- Frisian Omringdijk with Muiderslot as an outpost and with the objective of consolidating power in the newly conquered area. We have based our research on a method developed by Günter Bandmann, which proved to be practicable in the research into the significance of religious medieval buildings. On the strength of the outcome of our research based on the four categories of meaning distinguished by Bandmann: the historical, the allegorical, the symbolic and the aesthetic, we can conclude that especially the historical and allegorical categories of meaning offer a lot of leads. Particularly literary sources provide surprising insights here. It notably concerns the works written by the teacher of Floris V, Jacob van Maerlant, at Voorne under the authority of Aleid van Avesnes, the aunt at whose house Floris grew up. In our opinion the ideas and symbolism in the literary works of Van Maerlant are reflected in the type of castle chosen by Floris V and in his total concept of it. We think that in his castle-building programme Floris did not only express his power, but also his victory over the Frisians and the fact that he had avenged the murder of his father, the Roman Catholic king Willem II, by the West Frisians. In addition, he proved to aspire after a sovereign hereditary power, not an elected power as his father’s was. In his aspirations he expressed that he, as the son of a king, possessed the qualities which a good sovereign should have and that he thought he was entitled to the monarchy. In brief: we think that Floris V, just as the medieval commissioning authorities of religious buildings, deliberately gave significance to his profane buildings.